2016
DOI: 10.1055/s-0042-104060
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin D-K-Calcium Co-Supplementation on Endocrine, Inflammation, and Oxidative Stress Biomarkers in Vitamin D-Deficient Women with Polycystic Ovary Syndrome: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: The current study was conducted to assess the effects of vitamin D-K-calcium co-supplementation on endocrine, inflammation, and oxidative stress biomarkers in vitamin D-deficient women with polycystic ovary syndrome (PCOS). This randomized double-blind, placebo-controlled trial was performed on 60 vitamin D-deficient women diagnosed with PCOS aged 18-40 years old. Participants were randomly allocated into 2 groups to intake either 200 IU vitamin D, 90 μg vitamin K plus, 500 mg calcium supplements (n=30), or pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 40 publications
5
54
1
Order By: Relevance
“…This is consistent with current knowledge about the molecular effects of vitamin D on related pathways, such as the Nrf2 antioxidant pathway, which leads to activation of the glutathione-S-transferase A2 enzyme, and the antiaging protein Klotho (27,28). This is also consistent with the relationship between vitamin D deficiency and elevated markers of oxidative stress and the reduction of markers of oxidative stress with vitamin D supplementation in multiple populations (12,13,29).…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with current knowledge about the molecular effects of vitamin D on related pathways, such as the Nrf2 antioxidant pathway, which leads to activation of the glutathione-S-transferase A2 enzyme, and the antiaging protein Klotho (27,28). This is also consistent with the relationship between vitamin D deficiency and elevated markers of oxidative stress and the reduction of markers of oxidative stress with vitamin D supplementation in multiple populations (12,13,29).…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 88%
“…In other populations, vitamin D supplementation reduces markers of oxidative stress and also positively affects many other metabolic markers (12,13). Whether MS patients display a similar change in oxidative stress after vitamin D supplementation is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies were included in the present meta‐analysis which investigated the impact of vitamin D supplementation in 647 patients . The actual number of patients that were randomised in the various treatment groups is available in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, vitamin D's anti-inflammatory impact on human pathophysiology is well-accepted [100]. A current meta-analysis of randomized controlled trials concluded that vitamin D supplementation to women with PCOS results in an improvement in hsCRP, malondialdehyde, and total antioxidant capacity [95,96]; serum total testosterone and androstenedione levels were reportedly lowered in vitamin D-calcium cosupplement group as compared to the control group [101], in response to upregulated insulin receptor genes [102]. However, vitamin D does not affect the symptoms of hyperandrogenism [103].…”
Section: Other Immunological Mechanisms Of Pcosmentioning
confidence: 99%